(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2022)
With the growing amount of digital data, the world is moving towards providing faster and reliable sources for retrieving specific information from a vast amount of available data sources. Judiciary is one such field where the amount of data and information available online or offline is vast, courts need to have specific information from the vast available information quickly. Another need is to transform old offline data into digital information, which can be used for further processing and retrieval of information. The AI will not only smoothen the functioning of courts but will help the general public in accessing and using the legal information. Recently, India has proposed to introduce AI in the judiciary through various schemes. In this paper, we will look at what AI is and how it can be used in the judiciary. We will also look at e-courts, which is one such initiative by the Indian judicial system. We will look at more possible solutions that can be used by a judiciary system and we will conclude with pros and cons of AI in the judiciary system.